Evaluation of haemoglobin constant spring phenotypes and their haematological characteristics among high school students in Terengganu, Malaysia - Embong, Sharifatul F.; Adzahar, Sumaiyah; Daud, Adibah; Nordin, Mohammad Hudzaifah; Abdul Halim, Sarah; W. Embong, Wan Zuhairah; Rameli, Nabilah; Zulkeflee, Razan Hayati; Bahar, Rosnah (Saudi Arabian Armed Forces Hospital, 2025)
Objectives: To assess the prevalence of hemoglobin constant spring )Hb CS( in the Terengganu population, to evaluate the haematological parameters of individuals with heterozygous Hb CS, homozygous Hb CS, and compound heterozygous Hb CS, and to compare the effectiveness of high-performance liquid chromatography )HPLC( and capillary electrophoresis )CE( in detecting Hb CS. Methods: This study employed a cross-sectional design involving Form 4 secondary school students from Terengganu. Hemoglobin variants were analyzed using CE )CAPILLARYS2 Flex-Piercing System( and HPLC )VARIANT II(. Molecular testing, including multiplex polymerase chain reaction )PCR( and amplification refractory mutation system-PCR techniques, was carried out to detect alpha thalassemia mutations. Results: The prevalence of Hb CS revealed 92.2% heterozygous )mean zone 2 CE peak value of 0.7%(, 7.2% compound heterozygous )mean zone 2 CE peak value of 1.2%(, and 0.5% homozygous cases )mean zone 2 CE peak value of 4.5%(. Conclusion: The study highlights a significant prevalence of Hb CS among the Terengganu population, with heterozygous cases being the most common. The peak values in zone 2 CE varied significantly among the heterozygous, compound heterozygous, and homozygous HbCS cases, indicating the potential utility of these measurements in distinguishing between different clinical phenotypes.